RELATIONSHIP BETWEEN SPECIFIC GRAVITY OF CUPRIC SULFATE AND SATURATION OF BLOOD DROPLETS DURING DONORS’HEMOGLOBIN SCREENING - Resna Hermawati; Paulus Budiono Notopuro; Solichul Hadi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
There are several methods of hemoglobin screening. A technique that is practical, easy, and fast,as well as does not require high costs is needed for blood donor activities. Cupric sulfate method is still used in blood donor activities nowadays. There are several types of the specific gravity of cupric sulfate which will determine saturation speed. On the other hand, one of the requirements for a blood donor, according to the WHO, is that its hemoglobin level must be ≥ 12.5 g/dL. This research aims was to reveal how many blood droplets could be dripped into cupric sulfate solutions at certain specific gravities. This research was an observational analytic study using a cross-sectional design. One mL of venous blood sample was consecutively collected from thirty donors who came to the blood service of the Dr. R. Soedjono Selong Hospital in August 2017. Next, screening for hemoglobin levels was carried out on those blood samples using the cupric sulfate method with a specific gravity of 1.054. Autoanalyzer was also used as a reference method in this research. Results of cupric sulfate examination were categorized into sinking and non-sinking. The results of cupric sulfate examination with sinking category showed significant suitability with hemoglobin levels of >12.5 g/dL from autoanalyzer (p=0.002) with 100% sensitivity and 70.83% specificity. The results of cupric sulfate examination with non-sinking category (with daily replacement) showed a significant match with hemoglobin levels of >12.5 g/dL from autoanalyzer (p=0.003) with 68% sensitivity and 100% specificity. The use of ten samples in this research could reach 100% sensitivity and 100% specificity. Meanwhile, according to the WHO, 30 mL of cupric sulfate solution with a specific gravity of 1.053 can accommodate 25 donor blood droplets.Thus, it can be concluded that unlike the reference from the WHO of 25 droplets, based on hemoglobin screening test cupric sulfate solution with a specific gravity of 1,054 can be saturated with ten droplets.